Interkulturalitas dalam Pendidikan Multibahasa: Studi Perbandingan di Indonesia dan Negara ASEAN - Rachmawati, Dwita Laksmita; Rizqi, Ascosenda Ika; Malikha, Usrien (CV. Global Cendekia Inti, 2025)
The phenomenon of multilingualism in the ASEAN region reflects the dynamic interplay between local, national, and international languages, shaping social identities while simultaneously influencing educational policy. This study offers a comparative analysis of multilingual education policies and practices in Indonesia, Singapore, Malaysia, and Thailand, highlighting the integration of regional languages, the use of instructional languages in schools, and the structural challenges faced by each country. Employing a descriptive qualitative approach based on an extensive review of the literature, the research finds that Indonesia’s primary obstacles include disparities in educational resources, limited training for regional-language teachers, and the absence of a consistent curriculum for preserving local languages. In contrast, Singapore and Malaysia demonstrate notable success in implementing bilingual policies through structured integration of national languages with English. Thailand, meanwhile, continues to experience substantial gaps between urban and rural areas in the teaching and learning of English. The study’s findings underscore that the effectiveness of multilingual education depends on integrated policy frameworks, strengthened teacher training, the development of culturally grounded learning materials, and strategies capable of addressing social and geographical disparities. This research contributes to advancing inclusive and sustainable models of multilingual education across the ASEAN region.